2013
DOI: 10.1007/s40259-013-0068-8
|View full text |Cite
|
Sign up to set email alerts
|

CD30 as a Therapeutic Target for Lymphoma

Abstract: Hodgkin's lymphoma (HL) and ALK(+) anaplastic large-cell lymphoma (ALCL) have become highly curable due to the success of modern regimens of chemotherapy and radiotherapy. However, up to one-third of the patients experience relapse or do not respond to first-line therapy, and half of them relapse again after secondary therapy with limited options for further treatment. In the last 15 years, monoclonal antibodies (mAbs) directed to surface receptors became a new and valuable therapeutic option in many hematolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 198 publications
0
32
0
Order By: Relevance
“…The recent availability of brentuximab vedotin, an anti-CD30 monoclonal antibody, has led to improved OS and FFS rates among patients with refractory Hodgkin lymphoma, which is characterized by strong and uniform expression of CD30 [6]. A similar benefit was observed for patients with ALCL, a T-cell lymphoma also characterized by the strong and uniform expression of CD30 in neoplastic cells [7]. We previously reported that CD30 is expressed in ENKTL [8]; however, the significance of CD30 expression in ENKTL remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The recent availability of brentuximab vedotin, an anti-CD30 monoclonal antibody, has led to improved OS and FFS rates among patients with refractory Hodgkin lymphoma, which is characterized by strong and uniform expression of CD30 [6]. A similar benefit was observed for patients with ALCL, a T-cell lymphoma also characterized by the strong and uniform expression of CD30 in neoplastic cells [7]. We previously reported that CD30 is expressed in ENKTL [8]; however, the significance of CD30 expression in ENKTL remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…One of the earliest attempts was the development of an anti-CD30 monoclonal antibody called BerH2 and a single-chain variable fragment (scFv) linked to immunotoxins saporin-6 and pseudomonas exotoxin A, respectively [ 70 , 71 ]. A few other such therapies have since been trialled in various types of HL with some success [ 72 ], but the high reported toxicities make this unsuitable for ALCL. A similar approach that utilized an iodine-131 labelled murine anti-CD30 monoclonal antibody in HL achieved partial remissions [ 73 ], however toxicity was again found to be a barrier.…”
Section: Frontline Treatment For Paediatric Alclmentioning
confidence: 99%
“…As mentioned above, an alternative target for the treatment of ALCL regardless of ALK status, is CD30, which is consistently present on ALCL cells, yet is restricted to activated T and B cells under homeostatic conditions, thereby limiting the risk of off‐target effects. Early attempts at developing antibody‐based drug delivery of toxins, such as saporin‐6 or pseudomonas exotoxin A, or radioisotopes, such as iodine‐131, to CD30‐positive cells proved too toxic for the paediatric setting (Pasqualucci et al , ; Klimka et al , ; Schnell et al , ; Schirrmann et al , ). The arrival of the anti‐CD30 antibody, SGN‐30, conjugated to BV (or SGN‐35), an anti‐microtubule agent monomethyl auristatin E, which targets CD30‐positive cells and delivers the antimitotic drug, has shown promise.…”
Section: Current Avenues For Treatment; Breaking the Ceiling?mentioning
confidence: 99%